2021
DOI: 10.3389/fpsyg.2021.658027
|View full text |Cite
|
Sign up to set email alerts
|

When to Scaffold Motivational Self-Regulation Strategies for High School Students' Science Text Comprehension

Abstract: Noting the important role of motivation in science students' reading comprehension, this 14-weeks quasi-experiment investigated the optimal timing for implementation of metamotivational scaffolding for self-regulation of scientific text comprehension. The “IMPROVE” metamotivational self-regulatory model (Introducing new concepts, Metamotivation questioning, Practicing, Reviewing and reducing difficulties, Obtaining mastery, Verification, and Enrichment) was embedded at three different phases of secondary stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 72 publications
0
2
0
1
Order By: Relevance
“…Interventions that promote motivational regulation might also be a promising practice to consider as well (Michalsky, 2021). In a digital learning environment, Daumiller and Dresel (2019) found that both metacognitive and motivational regulation prompts were effective in improving task value, metacognitive control, task-related learning activities, and knowledge in a digital media learning environment.…”
Section: Implications For Practicementioning
confidence: 99%
“…Interventions that promote motivational regulation might also be a promising practice to consider as well (Michalsky, 2021). In a digital learning environment, Daumiller and Dresel (2019) found that both metacognitive and motivational regulation prompts were effective in improving task value, metacognitive control, task-related learning activities, and knowledge in a digital media learning environment.…”
Section: Implications For Practicementioning
confidence: 99%
“…Comprensión y alfabetización científica en la escuela: Revisión sistemática La mayor parte de estudios realizados corresponden al nivel secundaria y pocos los estudios que se centran en las características de la ciencia en el nivel primaria, siendo generalmente la metodología de investigación de tipo descriptivo interpretativo (Ezquerra et al, 2019;García-Carmona, 2021) necesario un andamiaje metamotivacional para que el estudiante regule y permita la reflexión de su aprendizaje (Michalsky, 2021) , lo que permitirá entender y comprender información de tipo científica a fin de tomar decisiones informadas integrando y evaluando el contenido de diversas fuentes, aspecto fundamental para convertirse en ciudadanos responsables que tomen decisiones acertadas (Feucht et al, 2021). El hecho de tener una buena comprensión lectora permite a una persona a nivel virtual tener mejores estrategias para poder seleccionar y discernir sobre sitio de internet que brinde credibilidad e información veraz a fin de mejorar la calidad de la argumentación así como un buen rendimiento científico (Castells et al, 2022;Cruz Neri et al, 2021a;Härtig et al, 2022).…”
Section: Idunclassified
“…Besides, people prefer to read a short document instead of a long one. Since motivation to understand a scientific text is of importance for readers, the simplified options depends on the motivation of readers [39]. Thus, the information in a summary designed for a scientist from a specific field should be different from that adapted for general public and we should take into account differences in narrative and information texts comprehension while evaluating the comprehensibility level of simplified texts in different readership.…”
Section: Information Selectionmentioning
confidence: 99%